2021
DOI: 10.1016/j.artd.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prior Fragility Fractures on Complications After Total Hip Arthroplasty: A Propensity Score–Matched Cohort Study

Abstract: Background: The impact of prior fragility fractures and osteoporosis treatment before total hip arthroplasty (THA) on postoperative complications is unclear. The purpose of this study was to characterize the effect of prior fragility fractures and preoperative osteoporosis treatment on short-term complications and secondary fragility fractures after THA. Methods: A propensity scoreematched retrospective cohort study was conducted using a commercially available database to (1) characterize the impact of prior f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The results of these study show significant associations between the 10-year probability of a MOF and HF calculated by FRAX and PPF in THA and TKA. Age and previous fracture, both components of the FRAX tool, seem to be major factors attributed to PPF risk which was seen in a high percentage among the studied patients and in previous publications 1 , 4 , 7 , 23 . Various studies showed that increased patient age is associated with the incidence of PPF 6 , 7 Previous fractures are associated with an increased PPF risk 23 .…”
Section: Discussionsupporting
confidence: 59%
“…The results of these study show significant associations between the 10-year probability of a MOF and HF calculated by FRAX and PPF in THA and TKA. Age and previous fracture, both components of the FRAX tool, seem to be major factors attributed to PPF risk which was seen in a high percentage among the studied patients and in previous publications 1 , 4 , 7 , 23 . Various studies showed that increased patient age is associated with the incidence of PPF 6 , 7 Previous fractures are associated with an increased PPF risk 23 .…”
Section: Discussionsupporting
confidence: 59%
“…Our findings are in accordance with prior orthopaedic literature, which has demonstrated that prior fragility fracture is strongly predictive of a subsequent fragility fracture, with up to 11.3% of patients sustaining a subsequent fracture within 3 years of their initial fracture. 11,16 In a similar study evaluating the effect of prior fragility fracture after primary THA, Ross et al 13 that prior fragility fracture increased the risk of subsequent fragility fracture, periprosthetic fracture, and allcause revision after a THA. These results call attention to the importance of risk stratification of patients before undergoing SA because periprosthetic fractures are a notable source of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperatively, surgeons may consider the use of stemless implants, which may decrease the risk of postoperative periprosthetic fracture. 13,17,18 Finally, in the postoperative period, decreasing the fall risk in this population by means of rehabilitation, dementia and delirium precautions, and home assistance all should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other authors have found increased risk of early revision for patients with higher ASA grades at primary surgery, 27 whereas our results indicate reduced risk at mid-late revision, which may be related to a state of poorer general health. Fractures in the pelvis, proximal/ humerus, wrist/forearm, spine or rib may be indicative of fragility, which are also known to increase risk of early revision; 28 patients without a history of these conditions may be at increased risk of mid-late term revision due to longevity. Other findings were a fourfold increased revision risk associated with malabsorption, but it is very rare with only 0.3% of patients having this comorbidity.…”
Section: Discussionmentioning
confidence: 99%